Serum C-reactive protein concentration in the management of infection in patients treated by continuous ambulatory peritoneal dialysis. Issue 4 (April 1985) - Hind, C R; Thomson, S P; Winearls, C G; Pepys, M B
Abstract : In a prospective study over 21 months, serum C-reactive protein (CRP) concentration was measured serially in 39 consecutive patients undergoing continuous ambulatory peritoneal dialysis. All patients with peritonitis mounted a CRP response, and the height of the response correlated well with the severity and extent of the peritoneal damage. Patients who recovered uneventfully after antimicrobial treatment showed a prompt fall in CRP from its peak value towards normal. In contrast, each patient in whom the serum CRP value remained raised after antimicrobial treatment had a complicated course. During routine outpatient follow up the serum CRP value remained within the normal range in the absence of intercurrent complications. These results, together with the commercial availability of rapid and precise assays for CRP, indicate that serial CRP measurements may be useful in monitoring the efficacy of antimicrobial treatment during episodes of peritonitis and in the recognition of intercurrent complications in patients undergoing continuous ambulatory peritoneal dialysis.